The social life of achievement - Long, Nicholas J.; Moore, Henrietta L., 1957- (Wyse series in social anthropology, 2013)
What happens when people "achieve"? Why do reactions to "achievement" vary so profoundly? And how might an anthropological study of achievement and its consequences allow us to develop a more nuanced model of the motivated agency that operates in the social world? These questions lie at the heart of this volume. Drawing on research from Southeast Asia, Europe, the United States, and Latin America, this collection develops an innovative framework for explaining achievement's multiple effects-one which brings together cutting-edge theoretical insights into politics, psychology, ethics, material